2014
DOI: 10.1177/2047487314557190
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic capacity of a clinically indicated exercise test for cardiovascular mortality is enhanced by combined analysis of exercise capacity, heart rate recovery and T-wave alternans

Abstract: The prognostic capacity of the clinical exercise test is enhanced by combined analysis of exercise capacity, heart rate recovery and T-wave alternans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…Since the FINCAVAS study contains records of thousands of patients and its results have already been published [14][15][16][17] we plan a future study to analyze the entire cohort with two major goals: (a) verifying the results of this study and past studies that were using the same software and (b) determining an optimal configuration for band limited ECG records which may enhance the performance of HFQRS for this specific configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the FINCAVAS study contains records of thousands of patients and its results have already been published [14][15][16][17] we plan a future study to analyze the entire cohort with two major goals: (a) verifying the results of this study and past studies that were using the same software and (b) determining an optimal configuration for band limited ECG records which may enhance the performance of HFQRS for this specific configuration.…”
Section: Discussionmentioning
confidence: 99%
“…For this study 132 ECG records of bicycle exercise tests were obtained from the FINCAVAS database [14][15][16][17].…”
Section: Analysis Groupmentioning
confidence: 99%
“…12,13 Overall, studies have shown that there is a graded continuum of risk and additive prognostic effect with the increase in the number and different combinations of abnormal exercise testing parameters and heart-rate-related measures. [14][15][16] In this issue of the European Journal of Preventive Cardiology, Chrysohoou et al aim to investigate the differential association of exercise testing related parameters with cardio-metabolic risk factors including diabetes, obesity, hypertension, as well as smoking. 17 The authors display numerous correlations between cardiovascular risk factors and exercise testing parameters that reflect inotropic and chronotropic response and exercise capacity; these factors include blood pressure and heart-rate reaction during exercise and recovery, exercise duration, and peak METs achieved.…”
Section: Barak Zafrirmentioning
confidence: 99%
“…3 However, the diagnostic and prognostic value of exercise ECG testing can be enhanced by incorporating in the assessment additional clinical data that exercise testing provides beyond the detection of ST-segment depression: exercise capacity, chronotropic and blood pressure response, heart rate recovery, calculation of the Duke treadmill score, T-wave alternans. [4][5][6][7] The diagnostic accuracy of exercise ECG can further be improved by analysis of the relation between ST-segment depression and heart rate changes during exercise and recovery. 8 Heart rate adjustment of ST-segment depression during exercise performed by calculating the ST-segment/heart rate (ST/HR) slope or the ST/HR index can improve the sensitivity with preservation of specificity, mainly from improved classification of patients with equivocal test responses related to up-sloping ST-segments.…”
Section: Jm Vrintsmentioning
confidence: 99%
“…[4][5][6][7] The diagnostic accuracy of exercise ECG can further be improved by analysis of the relation between ST-segment depression and heart rate changes during exercise and recovery.…”
mentioning
confidence: 99%